Management of IUGR With Ksheera Basti (AYUSHDHARA, 2024)
Number of cases of IUGR are increasing day by day and its treatment with Ayurveda is well established. Clinical trials are needed to support our treatment modalities on basis of modern parameters. Ayurveda has mentioned therapeutic utility of drugs like Shatavari, Madhuyashti, Ksheera and Ghrita and various routes of administration are advocated. In this context Ksheera Basti is highly recommended in our texts. Aims and objectives: To evaluate the efficacy of ksheera basti in management of IUGR. To assess the fetal weight gain and various maternal and fetal parameters after ksheera basti protocol. Methodology: Randomized clinical case series with 5 patients Result: Improvement was seen in maternal and fetal parameters in all 5 Patients. Discussion: In studying cases of IUGR, it was found that Ksheera Basti is much effective as a treatment protocol for IUGR. Marked improvement was seen in EFW, SFH, AC, FH AFI, maternal weight gain. Hence this therapy has capability to change the scenario and can prove as boom in field of Ayurveda in curing IUGR.